2014 Brazilian Symposium on Computer Games and Digital Entertainment 2014
DOI: 10.1109/sbgames.2014.33
|View full text |Cite
|
Sign up to set email alerts
|

A Non-intrusive Approach for 2D Platform Game Design Analysis Based on Provenance Data Extracted from Game Streaming

Abstract: The usage of provenance data drastically increases the potential for game data mining since it is able to record causes, effects and relationships of events and objects during a game session. However, it commonly requires modifications in the game engine in order to collect such provenance data. The modifications in the game engine may be unviable in commercial (and not open source) systems. In this paper, we propose a novel and non-intrusive approach for collecting provenance data in digital games. Our propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…To the best of our knowledge this work represents the only general approach for training automatic models for deriving player experience from gameplay video. Jacob et al (2014) represents the most related example of prior work. The researchers made use of a game-dependent image recognition method to collect logs of actions from gameplay video of Super Mario World.…”
Section: Related Workmentioning
confidence: 99%
“…To the best of our knowledge this work represents the only general approach for training automatic models for deriving player experience from gameplay video. Jacob et al (2014) represents the most related example of prior work. The researchers made use of a game-dependent image recognition method to collect logs of actions from gameplay video of Super Mario World.…”
Section: Related Workmentioning
confidence: 99%
“…The provenance support in SDM allowed for a broader range of analysis by using collected provenance information to generate a provenance graph [15]. In another work, Lidson et al [16] extracted provenance information using a non-intrusive technique through image processing mechanisms. In a more recent work, Kohwalter et al [17] also demonstrated the benefits of using the PinG approach during game analysis of serious games, helping students to understand the underlying reasons for an outcome.…”
Section: Introductionmentioning
confidence: 99%